2017
DOI: 10.1155/2017/4680650
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Specific MicroRNA Biomarkers for Noninvasive Early Cancer Detection

Abstract: Cancer is a complex disease residing in various tissues of human body, accompanied with many abnormalities and mutations in genomes, transcriptome, and epigenome. Early detection plays a crucial role in extending survival time of all major cancer types. Recent advances in microarray and sequencing techniques have given more support to identifying effective biomarkers for early detection of cancer. MicroRNAs (miRNAs) are more and more frequently used as candidates for biomarkers in cancer related studies due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Recent studies have demonstrated that microRNAs take crucial regulatory roles in many biological processes of human tumor including UM [19][20][21][22][23]. With the advances of sequencing techniques, growing computational studies aimed at identifying microRNAs biomarkers for the diagnosis and prognosis of cancers due to their regulation of target gene expression [24][25][26][27][28]. Furthermore, recent evidences suggested that the abnormal expression of microRNAs signifcantly correlated with the prognosis of UM patients and could be regarded as a potential target for treatment, like the previous demonstrated microRNAs: hsa-miR-374b-5p, hsa-miR-29c-3p, and hsa-miR-211-5p [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that microRNAs take crucial regulatory roles in many biological processes of human tumor including UM [19][20][21][22][23]. With the advances of sequencing techniques, growing computational studies aimed at identifying microRNAs biomarkers for the diagnosis and prognosis of cancers due to their regulation of target gene expression [24][25][26][27][28]. Furthermore, recent evidences suggested that the abnormal expression of microRNAs signifcantly correlated with the prognosis of UM patients and could be regarded as a potential target for treatment, like the previous demonstrated microRNAs: hsa-miR-374b-5p, hsa-miR-29c-3p, and hsa-miR-211-5p [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reproducible biomarkers are needed to predict the survival of patients with HCC at clinical settings. Based on bioinformatic studies, extensive evidence has been theoretically investigated to show that abundant target genes were regulated by miRNAs, which virtually involves in every process of malignant tumors pathway regulation, therapeutic strategy, and prognosis [26][27][28][29]. In particular, in the process of tumorigenesis and development, a large number of miRNAs play different roles as prognostic biomarkers, including lung cancer [30], breast cancer [31], colorectal cancer [32], prostate cancer [33], gastric cancer [34], and pancreatic cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…These cancer-screening tests are characterized by low sensitivities or specificities (PSA and fecal occult blood tests) or require specialized trained personnel (image related tests) that make them expensive and limit their use to specific populations and/or referral centers [14]. This is the reason by which blood biomarkers have been proposed as effective indicators to distinguish between cancer and normal conditions or among different cancer groups [15].…”
Section: Discussionmentioning
confidence: 99%